431 Chronic Opioid Use Prior to ACDF Surgery is Associated With Inferior Post-operative Outcomes. (1st April 2022) - Rodrigues, Adrian; Varshneya, Kunal; Veeravagu, Anand
Abstract : INTRODUCTION: Anterior cervical discectomy and fusion (ACDF) is widely used in patients with radiculopathy, myelopathy, or spondylosis. This patient population has a higher rate of opioid use than the general public, but dedicated studies on pre-operative ACDF opioid use have not been conducted. METHODS: The MarketScan Database was queried from 2007-2015 to identify adult patients who underwent an ACDF procedure using CPT codes. Patients were then classified into three separate cohorts based on the number of separate opioid prescriptions in the 12 months before their ACDF, excluding the 30 days immediately before their operation: (1) opioid naÏve if 0 prescriptions, (2) mild opioid use if 1-4 prescriptions, and (3) chronic opioid use if =5 prescriptions. Patients with a history of neck fracture or arthrodesis were excluded. Continuous insurance enrollment was confirmed for each patient. Short term outcomes were compared between groups, and nearest-neighbor propensity-score matching was employed to match patient cohorts across measured covariates. RESULTS: Of 81, 671 ACDF patients, 31, 312 (38.34%) were opioid naÏve, 30, 302 (37.10%) were mild users, and 20, 057 (24.56%) were chronic users. At baseline, chronic opioid users had more comorbidities than patients with less frequent opioid use (mean Charlson Comorbidity Index (CCI): 2.06; SD (2.06) vs. opioid naÏve mean CCI: 1.77; SD (1.79)). Chronic opioid users had higher rates of post-operative complications than mild and non-users (p < 0.0001), and higher rates of readmission and reoperation. After matching opioid naÏve vs. chronic opioid users along demographic, comorbidity, and intra-operative characteristics, post-operative complications remained elevated for chronic opioid users relative to opioid naÏve patients (9.13% vs. 5.29%; p < 0.0001). Rates of readmission and reoperation also remained higher for chronic opioid patients, as did inpatient costs. CONCLUSION: Chronic opioid users had longer hospitalizations and higher rates of post-operative complication, readmission, and reoperation, on average, than mild opioid and opioid naÏve users. After balancing patients across observed covariates, including comorbidity burden, the outcome differences persisted, suggesting a durable association between pre-operative opioid use and negative post-operative outcomes.